General agility and upper limbs agility in trained and untrained third-aged women - Sebastião Gobbi; Leandro Ferreira (Universidade Federal de Santa Catarina, 2003)
The objectives of this study were to verify the infl uence of training through generalized and supervised physical activities, on the general agility (GA) and upper-limb agility (ULA) of elderly women, in addition to verifying whether a relationship exists between these types of agility. Sixty women (59.7 ±5.9 years) were divided into two groups: a) trained group (TG) - participants of a supervised program of generalized physical activities, for at least one year, three weekly sessions of one hour each; b) an untrained group (UG) - with no practice of regular and supervised physical activities, besides every-day life activities. For GA evaluation, the agility and dynamic balance test designated by AAHPERD were applied and, for ULA, the plate tapping test designed by EUROFIT. The TG mean AAHPERD test time was 19.9 ± 2.7 seconds, and their EUROFIT Test TG score was 149 ± 23.2, while the UG achieved 21.7 ± 3.4 seconds on the AAHPERD test and scored 157 ± 24 points on the EUROFIT test. The difference between TG and UG was statistically signifi cant for the GA test, but the same was not true of the ULA test. The correlation between GA and ULA results was r=0.51. It is concluded that for elderly women: a) regular practice of general physical activities under supervision improves general agility level, but not upper-limb agility; b) general agility scores are poor predictors of upper-limb agility. RESUMO Este estudo teve como objetivos verifi car a infl uência do treinamento com atividades físicas generalizadas e supervisionadas, na agilidade geral (AG) e agilidade de membros superiores (AMS) em mulheres na terceira idade; bem como verifi car se existe relação entre esses dois tipos de agilidade. Participaram 60 mulheres (59,7 ± 5,9 anos) divididas em dois grupos: a) grupo treinado (GT) - participantes de um programa supervisionado de atividades físicas generalizadas, há pelo menos 1 ano, três sessões semanais de 1 hora; b) grupo não treinado (GNT) - não praticantes de atividades físicas regulares e supervisionadas. Para avaliação da AG aplicou-se o teste de agilidade e equilíbrio dinâmico da AAHPERD e, para avaliação da AMS, aplicouse o teste de toque em discos do EUROFIT. O GT apresentou valores médios de 19,9 ± 2,7 segundos para o teste da AAHPERD, e 149 ± 23,2 pontos para o teste do EUROFIT; enquanto o GNT apresentou valores médios de 21,7 ± 3,4 segundos para o teste da AAHPERD, e 157 ± 24 pontos para o teste do EUROFIT. Foram encontradas diferenças estatisticamente signifi cativas entre GT e GNT para o teste da AG, porém o mesmo não aconteceu para o teste de AMS. A correlação entre os resultados de AG e AMS foi de r=0,51. Conclui-se que em mulheres da terceira idade: a) a prática regular de atividades físicas generalizadas e supervisionadas melhora os níveis de AG, mas não a AMS; b) a medida de agilidade geral não é boa preditora da agilidade de membros superiores.